FORMULASI HUKUM PENYELENGGARAAN TELEMEDICINE SEBAGAI PENCEGAHAN RESIKO MALAPRAKTIK TERHADAP PASIEN - Fatihana Ulya Nasution (2023)
This study aims to determine the practice of implementing telemedicine in Indonesia and legal reformulation in telemedicine implementation as a prevention of malpractice risks to patients. This study used normative juridical research, with the statute approach, conceptual approach, and comparative approach. The data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. Primary legal materials were obtained from legislation, secondary legal materials were obtained from library studies and tertiary legal materials were obtained from dictionaries related to telemedicine and the legal implications that arise. The data analysis technique in this study was carried out qualitatively, with the specification of the research results being descriptive analytical. The results of this study indicate that Indonesia does not yet have regulations that specifically regulate the use of telemedicine. Regulation of the Minister of Health Number 20 of 2019 is not sufficient to guide the implementation of telemedicine in Indonesia. Thus, the use of telemedicine has the potential to cause various legal problems. If referring to the principles of medical practice, telemedicine can pose a risk of malpractice to patients because doctors do not examine patients directly. Not only that, current regulations also do not specifically regulate the concept of administering electronic medical records in telemedicine, thus increasing the risk of malpractice in the form of leakage of electronic medical record data and resulting in legal uncertainty in proving in the event of malpractice. Therefore, it is necessary to reformulate the law by issuing telemedicine regulations whose substance regulates the relationship between doctors and patients, the rights and obligations of the parties, protection of electronic medical records, criminal sanctions, and the establishment of an independent supervisory institution.